Clinical and morphological differential diagnosis of congenital hyperinsulinism before the stage of immunohistochemical study of paraffin-embedded specimens of pancreas in children - A. A. Perminova; L. B. Mitrofanova; A. A. Sukhotskaya; V. G. Bairov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2021)
Introduction.Differential diagnosis of various forms of congenital hyperinsulinism (CH) is required at the stage of urgent histological examination, but the difference between the exo- and endocrine parts of the pancreas in frozen sections is visualized very poorly.The objective was to search for differential diagnostic criteria of focal and diffuse forms of CH, suitable for urgent histological examination.Methods and materials. Pancreatic surgery material from 25 children with CH, of which 15 cases of focal form (FCH) and 10 cases of diffuse (DСH), and autopsy material from 10 children without CH (K). Frozen and paraffin sections stained with hematoxylin-eosin and histochemical stains were made from the tissue of the pancreas. The number of endocrinocytes with large nuclei was estimated in 10 fields of view for each case.Results. The average proportion of endocrinocytes with large nuclei was significantly (p <0.01) higher compared to the control both with FCH (in the affected area) and DCH (FCH – (1.82±0.50) %, DCH – (4.68±1.66) %, K – (0.34±0.21) %). We found a tendency to detect a higher absolute number of cells with large nuclei in DCH ((4.95±1.24) DCH and (3.71±1.56) FCH). Staining with azure-eosin, picro Mallory and the PAS reaction gave unstable result, and staining with toluidine blue and May-Grunwald did not allow differentiating exo- and endocrine parts of the pancreas.Conclusion. An increase in the size of the endocrinocyte nuclei was the unsuitable criterion for the differential diagnosis of CH forms, and histochemical stains did not give a stable qualitative result. For urgent biopsy examination, new immunohistochemical methods are needed.